Dark Triad and Religiosity: Competing Forces Shaping Ethical Perceptions of Accounting Students - Maylaffayza; Riswan Yudhi Fahrianta; Sri Ernawati; Jumirin Asyikin (Owner : Riset dan Jurnal Akuntansi, 2026)
Ethical breaches involving accountants have emerged as a significant issue in Indonesia, with various financial scandals exposing ongoing flaws in professional ethics. Even though there is conformity with International Education Standards (IES) 4, the way students view the effectiveness of ethics education is still notably low. This research examines how the desire for money, Machiavellian traits, narcissistic tendencies, and religious beliefs impact the ethical outlook of accounting students in Indonesian universities. A quantitative method was employed, gathering primary data via online surveys from 228 undergraduate accounting students who had taken a Professional Ethics course. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) through WarpPLS 8. 0 software. Results showed that Machiavellianism and narcissism negatively influence students’ ethical views significantly, while religiosity positively affects them. In contrast, the desire for money did not demonstrate a noteworthy impact on these ethical perceptions. The model designed accounted for 35% of the variance in ethical perceptions. These findings imply that religiosity serves as a protective moral factor that can lessen the harmful impacts of Dark Triad personality characteristics. The research highlights the necessity of incorporating ethical education and spiritual intelligence within accounting programs to enhance ethical awareness and integrity among future accounting professionals.